PERAN GURU DALAM MENINGKATKAN MINAT BELAJAR SISWA PADA MATA PELAJARAN BAHASA ARAB DI MIM 06 TEBLURU - Afif Muhilal; Afakhrul Masub Bakhtiar (STKIP Subang, 2023)
One of the compulsory subjects in Muhammadiyah schools is Arabic. However, in reality, many students are less interested in learning Arabic. Therefore, it is necessary to have the teacher's role in increasing students' interest in Arabic subjects. This study uses a descriptive qualitative approach. This method was chosen based on the nature of the data in the form of events, opinions and sentences with the efforts of observation, interviews and documentation. Based on the results of the study it can be concluded that Arabic teachers have a separate role in increasing the number of students. interest in learning shows this role in the form of a teacher, mentor and motivator. The functions of these three roles help increase students' interest in learning Arabic at MIM 06 Tebluru.